Identification and management of mycoflora associated with grain discolouration of rice (oryza sativa L.) - Aswathi M S (Department of Plant Pathology, College of Horticulture, 2018)
Grain discolouration is becoming a major problem of rice cultivation in recent years in India. This disease is prevalent in major rice growing tracts of Kerala. Since the disease directly affects the grains, it causes considerable yield loss. The extent of loss mainly depends on variety and climatic conditions. In Kerala, no systematic study has been conducted to identify the pathogens of grain discolouration which is essential for the effective management of the disease. Hence, this study was conducted to identify the pathogens causing grain discolouration of rice in Kerala and also to evaluate different management strategies. Purposive sampling survey was conducted in three rice growing districts of Kerala viz., Palakkad, Thrissur and Malappuram, covering 14 locations to study the occurrence of disease in farmers field. The incidence and severity of grain discolouration varied with the locations. Incidence varied from 6.8 to 100 per cent and severity varied from 21.47 to 95.49 per cent. Predominant rice varieties Uma and Jyothi were severely affected by the disease in all the locations. The common symptoms observed were brown to black discolouration of varying degrees ranging from brown to black spots to discolouration of entire glumes. The other symptoms were ash, cream and pink discolouration of glumes. The symptoms like brown blotches with creamy centre on the glumes and brown discolouration of glumes which later turned to cream colour from tip downwards were also noticed. Discolouration and deformation of the kernels were also observed in some cases. In severe infection chaffiness was observed. On isolation of the mycoflora associated with the grain discolouration, 62 fungal isolates were obtained. Pathogenicity of these fungal isolates, obtained from various locations was tested by artificial inoculation on susceptible variety Jyothi. Among these, 47 isolates were found pathogenic. The cultural and morphological characters studied revealed that these 47 isolates mainly comes under four genera viz., Curvularia, Bipolaris, Alternaria and Fusarium. Representative virulent isolates of these four genera were identified from Rajiv Gandhi Centre for Biotechnology (RGCB), Thiruvananthapuram as Curvularia lunata, Bipolaris oryzae, Alternaria alternata, Alternaria padwickii and Fusarium equisetii through molecular characterization. These pathogens were used for further studies. In vitro evaluation of biocontrol agents, Pseudomonas fluorescens and Trichoderma viride against the pathogens of grain discolouration revealed that both the biocontrol agents inhibited all the five pathogens significantly compared to control. T. viride inhibited all the pathogens (60-85%) significantly higher than P. fluorescens (12-16%). Among the seven fungicides tested in vitro, tebuconazole 250 EC (0.15%) and propiconazole 25 EC (0.1%) completely inhibited all the five pathogens compared to trifloxystrobin 25% + tebuconazole 50% WG which inhibited the growth of four pathogens completely and one pathogen by 87 per cent. The contact fungicide mancozeb 75 WP and the combination fungicide mancozeb 63% WP + carbendazim 12% WP inhibited two pathogens completely. Considering the overall performance, tebuconazole 250 EC and propiconazole 25 EC ranked first in their efficacy against Curvularia lunata, Bipolaris oryzae, Alternaria alternata, Alternaria padwickii and Fusarium equisetii. The biocontrol agents and fungicides were evaluated in the field, against grain discolouration of rice in kharif and rabi seasons of 2017-18 at RARS, Pattambi. Prophylactic application of talc based formulation of P. fluorescens as seed treatment (10g kg seed-1) + soil application (2.5 kg ha-1) + foliar spray (10g l-1) at booting or as seed treatment + soil application + foliar spray at 50% flowering was effective for the management of grain discolouration of rice and thereby improving the yield. The application of T. viride as seed treatment (10g kg seed-1) + foliar spray (10g l-1) at booting or as seed treatment + foliar spray at 50% flowering was also equally effective for the management of grain discolouration of rice and improving the yield. Among the fungicides tested in the field, tebuconazole 250 EC (0.15%) and propiconazole 25 EC (0.1%) were significantly superior in reducing the disease and increasing the yield followed by mancozeb 75 WP (0.3%), mancozeb 63% WP + carbendazim 12% WP (0.2%) and carbendazim 50 WP . The results of the present study revealed the wide spread occurrence of grain discolouration of rice in major rice growing districts viz., Malappuram, Thrissur and Palakkad of Kerala in all the predominant rice varieties. The major pathogens associated with the disease were identified as Curvularia lunata, Bipolaris oryzae, Alternaria alternata, Alternaria padwickii and Fusarium equisetii. The biocontrol agents, Pseudomonas fluorescens and Trichoderma viride were effective for the management of grain discolouration. The fungicides tebuconazole 250 EC (0.15%) and propiconazole 25 EC (0.1%) followed by mancozeb 75 WP (0.3%), mancozeb 63% WP + carbendazim 12% WP (0.2%) and carbendazim 50 WP were effective for the management of the disease.